2009
DOI: 10.1002/pbc.22027
|View full text |Cite
|
Sign up to set email alerts
|

Health status at long‐term follow‐up in patients treated for extremity localized Ewing Sarcoma or osteosarcoma: A Scandinavian sarcoma group study

Abstract: EBS survivors have poorer health status compared to age- and gender-matched controls. Long-term follow-up of these patients is therefore mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 51 publications
1
16
1
Order By: Relevance
“…Realistic and positive expectations lead to better health outcomes after surgical procedures [21], and so better data on what patients achieve in terms of sports performance after tumor surgery would be important. Furthermore, survivors of bone tumors pose a poorer health status compared with healthy control subjects [1] and physical training may provide beneficial effects on health like seen in cancer survivors in general [29,33]. In this study, we found moderate sports activity levels in patients after megaendoprosthetic reconstructions in the proximal femur, distal femur, and proximal tibia in the long term.…”
Section: Discussionmentioning
confidence: 48%
“…Realistic and positive expectations lead to better health outcomes after surgical procedures [21], and so better data on what patients achieve in terms of sports performance after tumor surgery would be important. Furthermore, survivors of bone tumors pose a poorer health status compared with healthy control subjects [1] and physical training may provide beneficial effects on health like seen in cancer survivors in general [29,33]. In this study, we found moderate sports activity levels in patients after megaendoprosthetic reconstructions in the proximal femur, distal femur, and proximal tibia in the long term.…”
Section: Discussionmentioning
confidence: 48%
“…Examples are cardiac toxicity from anthracyclines, hearing loss or tinnitus from cisplatin, infertility from alkylator therapy or radiation to the pelvis, endocrine complications usually from radiation to reproductive organs or the hypothalamic-pituitary axis, bladder dysfunction from chemotherapy and radiation, and second malignant neoplasms due to radiation and/or chemotherapy. [88][89][90][91][92] Postpubertal boys should be offered semen cryopreservation before initiation of therapy. Cryopreservation of oocytes or embryos (the latter requires use of donor sperm) is possible for postpubertal females but may delay treatment initiation.…”
Section: Late Effectsmentioning
confidence: 99%
“…A systematic literature review concerning the body image of children and adolescents conducted by Fan and Eiser found that adolescents seem to have more body image concerns than younger children and that males cope better than females with appearance changes. Despite the numerous late effects of bone sarcoma treatment and the fact that many patients are left functionally impaired or disabled , body image is rarely studied in relation to this cancer.…”
Section: Introductionmentioning
confidence: 99%